Prevalence of Olfactory and Other Developmental Anomalies in Patients with Central Hypogonadotropic Hypogonadism - Della Valle, Elisa; Vezzani, Silvia; Rochira, Vincenzo; Granata, Antonio R.; Madeo, Bruno; Genovese, Elisabetta; Pignatti, Elisa; Marino, Marco; Carani, Cesare; Simoni, Manuela (Frontiers in Endocrinology, 2013)
Introduction: Hypogonadotropic hypogonadism (HH) is a heterogenous disease caused by mutations in several genes. Based on the presence of hyposmia/anosmia it is distinguished into Kallmann syndrome and isolated HH. The prevalence of other developmental anomalies is not well established. Methods: We studied 36 patients with HH (31 males, 5 females, mean age 41.5), 9 with familial and 27 with sporadic HH (33 congenital, 3 adult-onset), by physical examination, smell test (BSIT Sensonics), audiometry, renal ultrasound, and magnetic resonance imaging of the olfactory structures. Results: Based on the smell test, patients were classified as normosmic (n=21, 58.3%) and hypo/anosmic (n=15, 41.6%). Hypoplasy/agenesis of olfactory bulbs was found in 40% of patients (10/25), (75% hypo/anosmic, 7.6% normosmic, p<0.01, Fisher’s-test). Remarkably, olfactory structures were normal in 2 anosmic patients, while 1 normosmic patient presented a monolateral hypoplastic bulb. Fourteen of 33 patients (42.4%) presented neurosensorial hearing loss of various degrees (28.5% hypo/anosmic, 52.6% normosmic, p=NS). Renal ultrasound revealed 27.7% of cases with renal anomalies (26.6% hypo/anosmic, 28.5% normosmic, p=NS). At least one midline defects was found in 50% of the patients (53.3% hypo/anosmic, 47.6% normosmic, p=NS), including abnormal palate, dental anomalies, pectus excavatum, bimanual synkinesis, iris coloboma and absent nasal cartilage. Anamnestically 4/31 patients reported cryptorchidism (25% hypo/anosmic, 5.2% normosmic, p=NS). Conclusions: Hypo-anosmia is significantly related to anatomical anomalies of the olfactory bulbs/tracts but the prevalence of other developmental anomalies, especially midline defects and neurosensorial hearing loss, is high both in HH and Kallmann syndrome and independent of the presence of anosmia/hyposmia. From the clinical standpoint Kallmann syndrome and normosmic HH should be considered as the same complex, developmental disease.